Two crows counting - Orgel, Doris; Moffatt, Judith (Milwaukee : Gareth Stevens Pub., 1996)
Two crows, one big and one small, count things they see from one to ten and then back down again.
"A Byron Preiss Book"
Originally published: New York : Bantam Doubleday, c1995.
Preschool-grade 1.
K-3
Keywords: Counting -- Juvenile literature; Crows -- Juvenile fiction; Stories in rhyme